Agreement between the Board of Regents of Higher Education and the Massachusetts Teachers Association NEA, July 1, 1983-June 30, 1986. - Massachusetts State Board of Regents of Higher Education, Boston; Massachusetts State Board of Regents of Higher Education, Boston; National Education Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
The collective bargaining agreement between the Massachusetts Board of Regents of Higher Education and the Massachusetts Teachers Association Chapter (1,747 members) of the National Education Association covering the period July 1, 1983-June 30, 1986 is presented. Items covered in the agreement include: definitions and unit recognition; paid and unpaid leaves of absence; insurance; travel expenses; tuition waiver; holidays; academic freedom and responsibility; department head selection and responsibilities; membership and responsibilities of the All-College committee; the college president's role; college committees; the student government association; staff performance evaluation; tenure; retrenchment and financial exigency; rights of retrenched staff; academic reorganization; grievance and arbitration procedures; evaluation workloads of faculty, librarians, Maritime Academy specialists; and campus school teachers; salaries; professional development program; sabbatical leaves; personnel files; no strike/lockout clauses; and appointment and promotion for faculty and library personnel. Appendices include: student instructional rating forms, personnel evaluation forms, and information on staff scholarship criteria. (SW)
Educational level discussed: Higher Education.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Collective Bargaining; College Faculty; Committees; Contracts; Department Heads; Employment Practices; Evaluation Criteria; Faculty Promotion; Faculty Workload; Fringe Benefits; Governance; Grievance Procedures; Higher Education; Job Layoff; Leaves of Absence; Librarians; Participative Decision Making; Personnel Policy; Questionnaires; Records (Forms); State Colleges; Student Evaluation of Teacher Performance; Teacher Participation; Teacher Salaries; Tenure; Unions; Massachusetts Board of Regents of Higher Education -- NEA Contracts; Financial Exigency -- Massachusetts Teachers Association -- National Education Association -- Personnel Files -- Tuition Benefit Programs; Legal/Legislative/Regulatory Materials; Tests/Questionnaires.